If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -5x(x + -1) = 20 Reorder the terms: 8x + -5x(-1 + x) = 20 8x + (-1 * -5x + x * -5x) = 20 8x + (5x + -5x2) = 20 Combine like terms: 8x + 5x = 13x 13x + -5x2 = 20 Solving 13x + -5x2 = 20 Solving for variable 'x'. Reorder the terms: -20 + 13x + -5x2 = 20 + -20 Combine like terms: 20 + -20 = 0 -20 + 13x + -5x2 = 0 Begin completing the square. Divide all terms by -5 the coefficient of the squared term: Divide each side by '-5'. 4 + -2.6x + x2 = 0 Move the constant term to the right: Add '-4' to each side of the equation. 4 + -2.6x + -4 + x2 = 0 + -4 Reorder the terms: 4 + -4 + -2.6x + x2 = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -2.6x + x2 = 0 + -4 -2.6x + x2 = 0 + -4 Combine like terms: 0 + -4 = -4 -2.6x + x2 = -4 The x term is -2.6x. Take half its coefficient (-1.3). Square it (1.69) and add it to both sides. Add '1.69' to each side of the equation. -2.6x + 1.69 + x2 = -4 + 1.69 Reorder the terms: 1.69 + -2.6x + x2 = -4 + 1.69 Combine like terms: -4 + 1.69 = -2.31 1.69 + -2.6x + x2 = -2.31 Factor a perfect square on the left side: (x + -1.3)(x + -1.3) = -2.31 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 4t+6t-2= | | 15+2x=7x-1-4 | | 2(y-4)=32 | | 9+3.5=11-3.5 | | 10x-2xy+4y=20 | | (3x+7)-(2x+5)= | | 7(b-2)=-19+6b | | 3x^2-54x-57=0 | | 8x+5+x=9x+7 | | 5(x+9)=5x+4 | | f-r=6f+26 | | 3/7g=8/11 | | 4+zy+3= | | z+15=22 | | 0.80(x-100)=97.93 | | Z/2-z/3 | | 3(-4)-4y=18 | | 0=-16t^2+140t+3 | | z/14=1 | | 8+18w=-44 | | y-19=-12 | | 9/12*1/2= | | 6x-4(-2x+9)=132 | | (7/4)11 | | 2n-(-25)=27n | | -5.5(4s+6)-2.2(2s-5)= | | 16-2x=-4x | | 4x+18=110 | | 7X+7Y=28+-7X+Y+28 | | N*4=9+n | | 4.8=x+(-6) | | n+2=5n+2 |